Pengaruh Pengaturan Processing Digital Radiography terhadap Kualitas Gambar pada Pemeriksaan Lumbosacral Posisi Lateral di Rumah Sakit Bhayangkara Makassar - Rini Hatma Rusli; Bambang Ariyanto (Pusat Riset dan Inovasi Nasional, 2022)
Optimal health services require supporting examinations in diagnosing a disease. On lumbosacral examination, radiograph quality is often less than optimal. Digital radiography is a new system on x-ray machines that has features for better image processing, one of which is flexible noise control (FNC). This study aims to determine the effect of digital radiography processing settings on image quality on lateral position lumbosacral examination. In this study using a qualitative descriptive method with an experimental or experimental research approach. The results showed that there was an effect of digital radiography processing settings on image quality with the FNC feature. This was shown by using the Image J application, there was a change in the standard deviation value before and after processing with the FNC feature. It is known that the FNC feature suppresses the noise value in the radiograph images.